Neither Born nor Made, but Socially Constructed: Promoting Interactive Learning in an Online Environment - Robinson, Bryan; López Rodríguez, Clara; Tercedor, Maribel (TTR, 2008)
AbstractThe social constructivist approach to translator training represents a clear statement on the importance of directing university teachers towards a student-centered, learning centered mode. By acknowledging the fundamental role of Vygotsky in determining his approach, Kiraly brought translator training in line with the established, broad-based humanistic approach to Foreign Language Learning; by drawing on Stevick and Schön, among others, he made this debt explicit.In this article, we apply the social constructivist approach through blended e-learning environments in courses offered to final year undergraduate students of translation. Our objective is to determine the success of combining technology and social constructivist pedagogy in promoting effective learner-centered learning. In Kiraly’s terms, we have “scaffolded” our instruction by applying instruments such as rating scales of criterion-referenced descriptors; textual and visual aids; and learner generated corpora. Our qualitative data is drawn from a variety of interactive formats: whole group online discussions, team-based online discussions, e-mail exchanges and specific “reflective” activities. We conclude that the quality of the “scaffolding” is essential to success in stimulating learning and that the e-learning environment is an excellent medium for the social constructivist approach.